Evaluación del efecto polinizador de las abejas (Apis mellifera) en cultivos convencionales y agroecológicos en el vivero de la ESPAM-MFL. - Vera Solórzano, Flor María (2018)
Bees are social insects, they live forming colonies that can be constituted by around 40,000 individuals and that are distributed in a very orderly food and work. Given the above, the research focused on the evaluation of the pollinating effect of bees in conventional and agroecological crops in the nursery of the ESPAM-MFL. For its effect, a completely randomized design was used (factorial DCA 2x3 with 3 replications). Cucumber (Cucumis sativus L.) conventional and agroecological crops were generated, with and without the intervention of bees (Apis mellifera) and the productivity of the cucumber was determined. Ten experimental units were adapted, 6 plots of 5mx2m located inside the closed greenhouse for treatments 1 and 2; and 4 plots of 15mx2m were adapted outside the greenhouse for treatments 3 and 4. The conventional agricultural methods included synthetic agrochemicals such as methamidophos, nonyl phenol, ethylene glycol and Urea and in the agro-ecological fertilizers and control of weeds of organic origin were used. The treatment that presented the highest number of fruits, weight and thickness per plants, was number 1 (presence of bees by conventional practices); while the treatment that presented lower values in the aforementioned variables was number 4 (absence of bees due to agroecological practices). The results described showed that the presence of bee pollination and the application of conventional techniques, favors the increase of fruits, weight and thickness of the cucumber. It is worth mentioning that without bees in the world, man would have a few years to live, since all trees with flowers and fruit producers would stop reproducing over the years; from which the importance and socio-environmental justification of this investigation is inferred.